Development of Functional Dawet Ayu with High Antioxidant Activity through the Addition of Torch Ginger Flower Powder with Foam Mat Srying Method - Naufalin, Rifda; Wicaksono, Rumpoko; Bawono, Icuk Rangga; Cahyani, Dwi Ari; Latifasari, Nurul; Hapsari, Rahajeng Tri; Saputri, Intan Ayu Andini Ganis (Indonesian Journal of Food Technology, 2025)
Background: The development of functional foods has encouraged innovation in traditional Indonesian products so that they provide not only nutritional value but also physiological health benefits. Dawet ayu, a starch-based traditional beverage, has potential to be developed into a functional drink by incorporating natural antioxidant sources, one of which is torch ginger (Etlingera elatior). Aim: This study aimed to develop dawet ayu as a traditional functional beverage with high antioxidant activity through the addition of torch ginger flower powder. Methods: The powder was produced using the foam-mat drying method to preserve bioactive compounds and was then applied in dawet formulations at various concentrations. The analyzed parameters included pH, color (L*, a*, b*), and antioxidant activity using the DPPH method. Results: The results showed that the addition of torch ginger powder had no significant effect on the color and pH of dawet ayu, but significantly increased antioxidant activity, with the IC₅₀ value decreasing from 739.3 ppm to 100.2 ppm at the highest concentration. The increase in antioxidant activity was attributed to the phenolic, flavonoid, and anthocyanin compounds present in torch ginger. These findings indicate that dawet ayu enriched with torch ginger powder has strong potential as a locally sourced functional beverage with both health and economic benefits. This product can be further developed as a natural-based functional drink.